Using simulations to investigate management decision making - Prohaska, Charles R; Frank, Ellen J (Simulation & Gaming, 1990)
Management researchers are always in search for new controlled environments from which they can gather data. This article proposes the use of total enterprise simulations as a research setting for studying management decision making. Using INTOP, the authors present examples of analyses that were conducted from a data base generated from the responses of executive MBA participants. Using a multiple regression, policy-capture approach, differences in the decision making strategies between groups are examined. Also discussed is an approach to developing a performance criterion that may be used when testing hypotheses regarding managerial decision-making effectiveness. The authorsconclude that total enterprise simulations represent a research setting that warrants further exploration. © 1990, SAGE Publications. All rights reserved.
Keywords: decision making; dept.mgt; management performance; policy capture; research methodology; simulation